Design and investigation of a bio-inspired ventilated flapping wing. (March 2015) - Zhang, GQ; Peyada, NK; Go, TH; Yu, SCM
Two types of the new wing design concept, namely the ventilated flapping wing have been proposed. It focuses on "ventilating" the wing during the upstroke motion so as to reduce the negative lift while increasing the net positive lift at each flapping cycle. The presence of the moving flaps can actually modify the flow pattern of the flapping wing significantly comparing with the solid wing case. The opening flaps can effectively increase the frontal areas in the airflow direction causing higher drag but at the same time generate lower negative lift during the upstroke. The vortical structures in the chordwise and spanwise directions at different positions together with the force variations around the wing have been obtained computationally and analyzed in details.